Current practice of postoperative fasting: results from a multicentre survey in China - Qianqian Zhu; Lifei Lai; Lianghua Zeng; Zhijing Yang; Yingling Zheng (BMJ Open)
Objective A gap between clinical practice and evidence is common. The present multicentre study was designed to explore the actual postoperative fasting practice, including the instructed fasting time from the ward staff and the actual postoperative fasting time.Design Multicentre survey.Setting Four tertiary hospitals in Shenzhen City, China.Participants A total of 988 patients completed a survey on instructed and actual postoperative fasting.Outcomes All patients received postoperative instructed fasting time from the ward staff. The median instructed fasting time for fluids from ward staff was 6 hours (IQR, 4–6 hours), and the median instructed fasting time for solid food was also 6 hours (IQR 5–6 hours) after surgery. The actual postoperative fasting time, including fluid and solid food intake, was significantly longer than the time recommended by the ward staff (both p<0.001).Results The median time to postoperative first flatus (FFL) was 16.5 hours (IQR 8–25.5 hours), and the median time to postoperative first faeces (FFE) was 41 hours (IQR 25–57 hours). The fasting time was significantly shorter than the time to FFL and the time to FFE, regardless of surgery type or anaesthesia type (all p<0.001). Postoperative nausea and vomiting (PONV) occurred in 23.6% of patients. After surgery, 58.70% of patients reported thirst, and 47.47% reported hunger. No ileus occurred.Conclusion Approximately half of the patients reported thirst and hunger postoperatively. Patients initiated oral intake earlier than the time to FFL or FFE without increasing serious complications. This study may support the rationale for interventions targeting postoperative oral intake time in future studies.